Keterkaitan Sifat Fisika Tanah Denganketahanan Tanaman Terhadap Penyakit - Harita, Reza Septa; Bawamenewi, Putri Harta (CV. SINAR HOWUHOWU, 2024)
This study aims to examine the relationship between soil physical properties and plant resistance to diseases. Soil physical properties, such as texture, density, and water-holding capacity, significantly influence plant health and their susceptibility to pathogen attacks. Using experimental methods involving the measurement of soil parameters and analysis of plant responses to various diseases, the results indicate that soils with optimal texture and aeration contribute to reduced infection rates. These findings suggest that proper management of soil physical properties can enhance plant resistance, providing important implications for sustainable agricultural practices. The study advocates for an integrated approach to soil management to improve plant resilience against diseases, ultimately leading to increased agricultural productivity.